Penurunan Nilai Suku Cadang yang Tersimpan pada Persediaan PT. X - Jonathan Peter Joyodiono; I Gede Agus Widyadana (Jurnal Titra, 2017)
PT. X. is a multinational company that produces consumer goods. The main goal of this study is to reduce the value of unused sparepart on the inventory by creating a database, and also improving material cleansing mechanism for nonmoving sparepart that leads to optimal inventory cost for Technical Material Management, sub-department of Supply Chain Planning in PT. X. this sub-department is in charge on technical materials and its management that include purchasing plan, sparepart usage recording, etc. Database is built for west and east plant using Microsoft Access 2013. Material cleansing improvement only held in east plant and start from the segregation that has a huge contribution to PT. X inventory cost.